(untitled) (Research, Society and Development, 2020)
Dengue is a which spread rapidly attracted the attention of public authorities in Brazil in the 1990s. The arboviruses are transmitted by mosquitoes of the genus Aedes such as Aedes aegypti, are associated with serious epidemics of febrile diseases in tropical regions of the world. This virus has become a worrying public health problem, due to the high annual incidence. Infections are generally asymptomatic but when symptomatic, they evolve to cure or to hemorrhagic / neurological conditions. This study aimed to verify the prevalence of Dengue transmission through the Aedes aegypti vector in the years 2015 to 2019 in Piauí. The research is descriptive, quantitative, retrospective and transversal. Data were collected in the Sistema Nacional de Informação de Agravos de Notificação (SINAN). Based on the collected data, 28.219 cases of Dengue were reported with no significant difference in percentages in relation to gender, as for the age group, there was a prevalence of people from 20 to 39 years old. Regarding classification, most notifications did not specify the serotype. A predominance of cases of cure was identified with some blank notification fields. It is concluded that the susceptibility to the Dengue virus is universal, with a prevalence value of 8.57/1000 population with studies and discussions of epidemiological data about it and reinforcement of prevention. Are appointed as reflections the raise of awareness from the professionals in charge of doing the notifications of Diseases of Compulsory Notification in SINAN, as being mandatory to fill in all fields of the form.